2020
DOI: 10.36706/altius.v9i1.11492
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Latihan Self Talk Dan Imagery Relaxation Terhadap Konsentrasi Dan Akurasi Tembakan 3 Angka Cabang Olahraga Bolabasket

Abstract: Abstract. This study aims to determine the effect of self-talk and Imagery relaxation exercises on the concentration and accuracy of 3point shoot in basketball. The method used in this study was an experimental design with two groups pretest-posttest design. The subjects in this study were 12 young basketball athletes with 6 male and 6 female with purposive sampling, who were divided into two groups of experimental groups with match subject ordinal pairing (MSOP) based on the ranking of tembakan 3 angka accura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 1 publication
(1 reference statement)
1
3
0
4
Order By: Relevance
“…These results are in line with the research stating that self-talk helps the athlete's performance since it has a significant effect on increasing motivation and self-confidence and helps prepares the athletes for competition [26]. Many other studies have indicated that self-talk exercise is one of the methods for increasing the athlete's self-confidence and efforts to improve performance [7], [10]; a strategy that is considered to be the most appropriate technique in improving the performance of the athletes [8], [27]; to control emotions and concentration [28]; and also helps the athletes reduce distractions to be more focused [27].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…These results are in line with the research stating that self-talk helps the athlete's performance since it has a significant effect on increasing motivation and self-confidence and helps prepares the athletes for competition [26]. Many other studies have indicated that self-talk exercise is one of the methods for increasing the athlete's self-confidence and efforts to improve performance [7], [10]; a strategy that is considered to be the most appropriate technique in improving the performance of the athletes [8], [27]; to control emotions and concentration [28]; and also helps the athletes reduce distractions to be more focused [27].…”
Section: Discussionsupporting
confidence: 89%
“…The accuracy in petanque is an important aspect in winning [31], [7], because the point calculation is done based on the shooting results. Therefore, it requires athletes to have a high level of accuracy in shooting, and in order to improve this, one of the given mental exercises is self-talk [32].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Perkembangan mental atlet tidak kurang pentingnya dari perkembangan fisik, teknik dan taktik, apabila mentalnya tidak dapat berkembang, prestasi yang tinggi tidak akan dapat dicapai (Hidayat, 2011). Seperti yang kita tahu bahwa kepercayaan diri merupakan aspek penting dalam perkembangan eksklusif atlet yang perlu ditingkatkan serta salah satu metode yang digunakan yaitu menggunakan selftalk (Pratama et al, 2020). Adapun self-talk artinya salah satu strategi psikologis yg digunakan oleh para atlet serta pelatih, oleh karena itu self-talk bisa meningkatkan kemampuan dan performa atlet pada olahraga, self-talk yg digunakan pada keadaan tertekan, cemas, marah seringkali tidak terkendali dan tidak masuk akal sebab atlet pasti tidak menyadari dengan apa yang sudah diungkapkan (Komarudin, 2016).…”
Section: Pendahuluanunclassified
“…Model latihan soft toss ball melatihkan para pemain untuk menyesuaikan arah bola yang datang dari pemain atau pelatih yang memberikan umpan dengan objek yang selalu berubahubah tentu pukulan yang dilakukan akan menyesuaikan dengan bola yang datang, keadaan seperti ini akan memperkaya gerakan para pemain dalam melakukan pukulan sehingga dalam permainan akan mampu mengaplikasikan pengalaman yang diterima tersebut dalam Qory Jumrotul Aqobah, Masnur Ali, Arifin Ika Nugroho keterampilan memukul. Latihan soft toss ball dapat diterapkan dalam bagian dari latihan imagery, latihan imagery dapat membantu para pemain untuk dapat memvisualisasikan gerakan dan bermanfaat dalam meningkatkan keterampilan (Pratama, Hardiyono, & Pasaribu, 2020).…”
Section: Pembahasanunclassified